Forty years of populism in the European Parliament - Manucci, Luca (2021)
In May 2019, the elections for the European Parliament (EP) saw populist parties obtain almost a third of the available seats, with populist radical right parties making the biggest gains compared to the 2014 elections. Despite the results were less resounding than some predictions anticipated, a considerable amount of Members of the EP represent a populist party. This article first presents the performance of populist parties in forty years of EP elections, from their first occurrence in 1979 until 2019, and then focuses on populist radical right parties. The analysis suggests that (i) the number of seats occupied by populist parties in the EP continues to grow over time; (ii) right-wing populist parties no longer struggle to form political groups within the EP; (iii) radical right populist parties have become the most common type of populist party within the EP.